Management of Education Services for Children - Istaryatiningtias, Istaryatiningtias; Daliman, Daliman (Journal of Education Reseach and Evaluation, 2021)
This research was motivated by the fact that the quality of management education services for deaf children has not been fulfilled. This research is important to do to determine the quality of education service management for children with hearing impairment. The research method used by researchers is descriptive qualitative research. In this study the authors found the results of their research; (1) Old buildings that cost money. (2) Teacher competition in controlling the Maternal Reflective Method (MMR) is caused by weak knowledge, skills and abilities in providing educational services to children with hearing impairment. (3) The condition of speech building teachers and voice and rhythm perception communication coaches (PKPBI) is less skilled in quality and quantity, and there are still many teachers who are retired and transferred. The conclusion of this research can be seen that the planning, organizing, movement, supervision and service have been implemented properly.